Adsorption of Crystal Violet with Magnetic Graphene Oxide Nano Adsorbent Synthesized from Schima wallichii Wood - Danar Arifka Rahman; Mindriany Syafila; Qomarudin Helmy (Indonesian Journal of Chemistry, 2024)
The textile industry continues to experience production developments to reach a target for the country's economic development. The increase in production leads to an increase in the amount of waste generated. Dyes such as crystal violet (CV) in textile wastewater are toxic and difficult to remove by conventional treatment. Adsorption with nano adsorbent has been widely researched and developed to remove dyes in the environment because it has various advantages. Magnetic graphene oxide (GO-Fe3O4) as a006E adsorbent has been widely studied because it has a large surface area, strong chemical bonds and is easily separated from the aqueous phase. Puspa (Schima wallichii) wood has the potential to be used as a natural source of graphite. The characterization of the adsorbent was tested with FTIR, SEM-EDS, and BET. The equilibrium time for the adsorption process was 20 min, while the optimum adsorbent dose was 0.04 g. Adsorption isotherm and kinetics analysis showed that CV adsorption using MGO followed Langmuir and pseudo-second-order models, respectively. Thermodynamic studies displayed that the CV adsorption was endothermic and spontaneous. The results of this study suggested that the adsorption of CV using GO-Fe3O4 nano adsorbent from S. wallichii wood proceeds by chemisorption and physisorption.